Analisis Pengaruh Kinerja Karyawan Terhadap Kepuasan Pelanggan di Mitra Bangunan Dion Putra Wonogiri - Sholihah, Atika Nur Maratu; Yani, David Ahmad (Business and Enterpreneurship Journal (BEJ), 2025)
The background of this research is that every business competitor wants success in managing business. In order to remain superior and innovate, company is required to meet the wants and needs and quality of service to customers. That way customers feel satisfied and valued so they are willing to become regular customers. This study has aim of observing  influence of employee performance Dion Putra Building Partners on its customers. To describe and explain in detail the effect of employee performance in the store on customer satisfaction, this study uses descriptive method with a survey approach. The measuring instrument used is Likert scale with the independent variable employee performance and dependent variable customer satisfaction. Collection techniques by distributing questionnaires and interviewing 15 respondents. Data analysis used in this study is validity test, reliability test and analysis, then the coefficient of determination is carried out to determine the effect of employee performance on customer satisfaction. Validity test shows that the research is valid. Reliability test shows that the research is reliable. Regression analysis results show an F value of 181.336 with a significance of 0.000 and coefficient of determination of 0.928 (92.8%). With this research if customers are dissatisfied with the service, store employees can improve service quality and find solutions to what efforts can improve quality of service to customers. Keywords : Customer satisfaction, performance, service quality